ANALISIS RISIKO HARGA KOMODITAS CABAI PADA PASAR TRADISIONAL DAN MODERN DI SULAWESI SELATAN - Fatmawati Akib; Sri Mardiyati; Nurdin Mappa; Mohammad Natsir; Muh. Arifin Fattah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
Chili is a commodity or horticultural crop with significant economic value in Indonesia. Price issues for chili commodities continue to occur. There are indications that chili prices fluctuate in Indonesia over a certain period. This study aims to determine chili price fluctuations and trends, chili price risks, and compare the level of chili price risk in traditional and modern markets in South Sulawesi Province. This type of research is quantitative. The type of data in this study is secondary data (time series). The data sources are the Strategic Food Price Information Center (PIHPS) and the Central Statistics Agency (BPS) of Makassar City, South Sulawesi. The data collected are chili commodity prices in modern and traditional markets from January to December 2024. Data analysis techniques include multiple linear regression analysis (trend analysis) to determine chili price trends, calculation of the coefficient of variation to analyze price risk, and partial testing using the t-test to compare price risk levels. The results show that the price trend of large red chilies, curly red chilies, and red cayenne peppers in traditional and modern markets has experienced a downward trend with a relatively low level of price fluctuation. The price risk of large red chilies, curly red chilies, and red cayenne peppers, based on the coefficient of variation analysis, shows a coefficient of variation (CV) value > 0.5, indicating that these three chili commodities do not have a high price risk. A comparison of the price risk level of large red chilies in modern markets shows a calculated t value of -6.418 > t table 1.984, curly red chilies have a calculated t value of -9.008 > t table 1.984, and red cayenne peppers show a calculated t value of -6.249 > t table 1.984. This means that there is a significant difference in the price risk of red cayenne peppers between traditional and modern markets.